2018
DOI: 10.1111/dth.12701
|View full text |Cite
|
Sign up to set email alerts
|

A case series of dupilumab-treated allergic contact dermatitis patients

Abstract: Atopic dermatitis is characterized by skin barrier abnormalities and immune dysregulation with increased TH2 signaling playing a central role. Investigations of allergic contact dermatitis suggest that certain allergens may also activate particular T cell signatures such as TH2‐dominant responses to fragrance and rubber. We present a case series of patients with allergic contact dermatitis who were successfully treated with dupilumab, a biologic developed for atopic dermatitis that dampens TH2 signaling. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…8 Although FDA-approved only for atopic dermatitis, asthma, and chronic rhinosinusitis with nasal polyposis, dupilumab has shown efficacy in several dermatologic diseases of the type 2 inflammatory pathway, including allergic contact dermatitis, bullous pemphigoid, and prurigo nodularis. [9][10][11] In summary, our patient experienced a dramatic and lasting improvement with dupilumab. Although further studies are certainly necessary to assess the true benefit of this medication for EAE and other eosinophilic dermatoses, dupilumab offers a mechanistically compelling therapy for an often refractory condition.…”
Section: Abstract Case Report Figure 1 Erythematous Plaques On the Extensor Surfaces Of The Forearmsmentioning
confidence: 60%
“…8 Although FDA-approved only for atopic dermatitis, asthma, and chronic rhinosinusitis with nasal polyposis, dupilumab has shown efficacy in several dermatologic diseases of the type 2 inflammatory pathway, including allergic contact dermatitis, bullous pemphigoid, and prurigo nodularis. [9][10][11] In summary, our patient experienced a dramatic and lasting improvement with dupilumab. Although further studies are certainly necessary to assess the true benefit of this medication for EAE and other eosinophilic dermatoses, dupilumab offers a mechanistically compelling therapy for an often refractory condition.…”
Section: Abstract Case Report Figure 1 Erythematous Plaques On the Extensor Surfaces Of The Forearmsmentioning
confidence: 60%
“…Conversely, a few cases of severe ACD have been dramatically improved by dupulimab, and this therapy can influence patch test results in some patients. Goldminz et al reported a case series of three patients with ACD who were successfully treated with dupilumab . Two of them had no history of AD during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent literature about clinical effects of dupilumab on ACD varies from complete clearance of ACD to continuing recalcitrant lesions. 8,9 Although the underlying immunological pathways in ACD and AD are not the same, they are largely overlapping. This might explain why targeting the shared Th2 pathway could reduce ACD severity.…”
mentioning
confidence: 99%